Study of Electric Field Impact on Crystallization in Tunnel Drainage Pipes in Hard Water Area - Liangwen Wei; Jingyi Guo; Xuefu Zhang; Yunqi Li; Peng Huang (Advances in Civil Engineering)
To solve the problem of blockage of crystallization in tunnel drainage pipes in hard water area, electric field devices are designed and applied in the transversal tunnel drainage pipe according to the fundamental law of crystallization. Laboratory tests were carried out to test the crystallizing tunnel drainage pipe under the effect of electric field in order to study the law of electric field impact on crystallization in tunnel drainage pipes in hard water area. The test results indicate that the arranged circumferential and parallel plate electric field devices can form an electrical field within a narrow and small space inside the pipe and influence the ion movement in water and adsorption performance between crystals and the pipe. Under the condition of full flow, the amount of crystals in the ordinary pipe without electric field treatment increases progressively along water flow direction and remains relatively uniform later. The amount of crystals along the water flow direction of the pipe treated with circumferential and parallel plate electric fields presents signs of fluctuation in the early stage and then stableness later. The amount of crystals in the fluctuating section is higher and lower in the uniform section, and its uniform section length is longer than that in ordinary pipes. Under the condition of full current, crystallizing speed declines with elapse of running time. After the electric field is imposed, crystallizing acceleration progressively decreased to a relatively lower level. Comparing three voltages of 5 V, 12 V, and 24 V, the effect of scale inhibition under 5 V is superior. When water amount in the pipe varies, the effects of scale inhibition under different electric field modes are different. The electric field effect causes the changes of the external form of calcium carbonate crystal and its surface abrasion, porous crystal, and structural looseness.